Pengembangan Ekonomi Kreatif Dalam Meningkatkan Pendapatan Masyarakat Matawolot Kab.Sorong - Ayu Lestari; Syahrul Syahrul; Rokhimah Rokhimah (Prodi Ekonomi Syariah IAIN Sorong, 2022)
Creative Economy Development in Increasing the Income of the Matawolot Community Kab. Sorong,. The problems raised in this study are, 1) how to develop a creative economy in increasing the income of the Matawolot community, Sorong Regency? 2) What is one type of creative economy carried out by the Matawolot community, Sorong Regency? 3) what are the obstacles faced in developing the creative economy carried out by the Matawolot cracker processors in Sorong Regency? The method used in this research is a qualitative method, with a case study approach. The method of data collection is done by the process of observation, interviews, and documentation. In analyzing the data, the researcher used descriptive qualitative data analysis. The results of this study that; 1) How to develop the creative economy of cracker business groups to help increase people's income, one of which is marketing on social media such as Facebook, WhatsApp and so on. Because by doing and composing in packaging and marketing techniques can experience very rapid development for the future the amount of income earned by each processed cracker craftsman in Matawolot Village has increased, and the amount of income received is based on how many cracker products are produced; 2) as for one type of creative economy carried out by the Matawolot community, including this cracker business group which is a home industry in Matawolot Village which has problems including techniques in the marketing process which are still by stocking the kiosk to be deposited how much amount required.